Public Life of Poles Through the Prism of Surveillance by Repressive Structures of the South-Western Region of the Russian Empire on the Eve of the First World War - Ivanenko, O. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2022)
This paper, based on documents from the Central State Historical Archive of Ukraine (Kyiv), highlights the specifics of the social life of Poles in the South-Western region of the Russian Empire on the eve of the First World War. The author studied the official correspondence of the General Staff of the Russian Empire and the Staff of the Kyiv Military District, the Ministry of Internal Affairs and provincial gendarme departments of the South-Western Region, secret documents of the Kyiv Security Office, the Office of the Kyiv, Podillya and Volyn Governor-General, and so on. These documents illustrate the focus of the Russian imperial authorities on gathering information about the political situation and public sentiment in Austria-Hungary, and above all in Galicia. In the late 19th and early 20th centuries, against the backdrop of an intensified interstate confrontation between Austria-Hungary and Russia, a competition of state building models became more active. In the early 20th century, the idea of federalism was strengthened in Austria-Hungary with the aim of internal political stabilisation and a broad guarantee of the Slavonic peoples’ rights. And it was no accident that guard and punitive authorities of the Russian Empire focused their attention on intelligence information about the activities of the Polish Socialist Party, the creation of paramilitary organizations in Galicia, and the preparation of an anti-Russian uprising by the Poles during the expected war between Russia and Austria-Hungary. The Polish population of the South-Western region was supervised. Discriminatory measures were taken against the cultural activities of the Poles of the South- Western region aimed at raising national self-awareness and patriotism, schooling and national-cultural public organizations were suppressed, and monitoring of the Roman Catholic clergy was established. In view of the approach of the 50th anniversary of the January Uprising of 1863–1864, the guard and punitive bodies of the Russian Empire directed special efforts to prevent the spread in the South-West Region of actions commemorating this symbolic anniversary organized on the territory of Austria-Hungary, in particular in Lviv. У цій статті на базі документів фондів Центрального державного історичного архіву України м. Києва висвітлюються особливості громадського життя польської громади Південно-Західного краю Російської імперії напередодні Першої світової війни. Документи Центрального державного історичного архіву України, зокрема офіційне листування Генерального штабу Російської імперії і штабу Київського військового округу, міністерства внутрішніх справ і губернських жандармських управлінь Південно-Західного краю, документи з грифом «цілком таємно» київського охоронного відділення, канцелярії київського, подільського й волинського генерал-губернатора тощо, відображають націленість державних органів Російської імперії на збирання інформації про політичну ситуацію й настрої громадськості в Австро-Угорщині, й насамперед Галичині. Наприкінці ХІХ — на початку ХХ ст. на тлі загострення міждержавного протистояння Австро-Угорщини та Росії актуалізувалася й конкуренція моделей національно-державного будівництва. У самій Австро-Угорщині на початку ХХ ст. зміцнювалася ідея федералізму, трансформації дуалістичної держави в триалістичну як інструменту внутрішньополітичної стабілізації і ширшого забезпечення прав слов’янських народів. І невипадково охоронно-каральні органи Російської імперії фокусували свою увагу на агентурній інформації щодо діяльності Польської соціалістичної партії, створення в Галичині парамілітарних організацій і підготовки антиросійського повстання поляків під час очікуваної війни Росії і Австро-Угорщини. Встановлювався нагляд за польським населенням Південно-Західного краю. Здійснювалися дискримінаційні заходи щодо культурницької діяльності поляків, спрямованої на піднесення національної самосвідомості й патріотизму, утискалося шкільництво й національно-культурні громадські організації, встановлювалося стеження за римо-католицьким духівництвом.